A macrophage attack culminating in microthromboses characterizes COVID 19 pneumonia - Brian S. Bull; Karen L. Hay (Immunity, Inflammation and Disease, 2021)
Abstract Introduction A neutrophilic infiltrate characterizes bacterial pneumonia. Macrophage infiltration is similarly characteristic of the viral pneumonia caused by SARS‐CoV‐2. These infiltrating macrophages, while phagocytic and capable of engulfing virus laden alveolar cells, are also rich in tissue factor—a thromboplastin. This prothrombotic aspect likely explains how a respiratory virus whose malign effects should be confined to the oropharynx, bronchi and lungs, can cause a panoply of extra‐pulmonary organ disorders. Elevated ferritin levels in ICU Covid 19 patients, and elevated acute phase proteins suggest immune overreaction. Elevated d‐dimers implicate clotting as well. This evidence links hyperactive innate immunity (macrophage lung infiltrates) with the elevated levels of oligomeric fibrin present in the bloodstream of these patients. Methods An in‐house assay measuring oligomeric (soluble) fibrin (also referred to as soluble fibrin monomer complexes or SFMC) in whole blood, previously developed for monitoring incipient disseminated intravascular coagulation (DIC) during liver transplantation, was made available to COVID ICU attendings. Since SFMC constitutes the input to intravascular fibrin clots and d‐dimer reflects fibrin clot dissolution, it was thought that the two tests, run in tandem along with assays of immune activation, might clarify the frequency and possibly the cause of DIC in patients with severe COVID‐19 pneumonia. Results Classical DIC with intravascular clotting and thrombocytopenia was documented only rarely. However, early in the pandemic shortly after the assay was made available, it identified three patients undergoing acute defibrination. In each patient virtually all of the body's fibrinogen was transformed into SFMC over 3–4 days and deposited somewhere in the vasculature without any gross clots being detected. Conclusions Three COVID‐19 patients with evidence of a hyperactive immune response (elevated ferritin and acute phase proteins) defibrinated while blood levels of SFMC were being monitored. SFMC levels that were five times higher than normal appeared in the circulation during the defibrination process. SFMC at these levels may precipitate as showers of microclots, damaging heart, kidney, brain, and so forth.